1999
DOI: 10.1074/jbc.274.22.15662
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Inhibitor of Nuclear Factor-κB, RelA-associated Inhibitor

Abstract: Here we report the identification and characterization of a novel protein, RelA-associated inhibitor (RAI), that binds to the NF-B subunit p65 (RelA) and inhibits its transcriptional activity. RAI gene was isolated in a yeast two-hybrid screen using the central region of p65 as bait. We confirmed the physical interaction in vitro using recombinant proteins as well as in vivo by immunoprecipitation/Western blot assay. RAI gene encodes a protein with homology to the C-terminal region of 53BP2 containing four con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
160
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 39 publications
0
160
0
Order By: Relevance
“…Notably, iASPP is most phylogenetically conserved from worm to human by sharing 38% amino acid identity and 78% similarity in the ankyrin repeats and SH3 domian and only ASPP family member that identified in Caenorhabditis elegans-lower organism (Bergamaschi et al, 2003). Originally, iASPP was identified as a Rel A/ p65 associated inhibitor (RAI) of 315 amino acids in length (Yang et al, 1999). Subsequent studies demonstrated full length of RAI protein, iASPP containing 828 amino acids in humans and in C. elegans its homologoue is named as Ce-iASPP containing 769 amino acids encoded by ape-1 gene (Bergamaschi et al, 2003;Slee et al, 2004).…”
Section: The Aspp Family Genesmentioning
confidence: 99%
“…Notably, iASPP is most phylogenetically conserved from worm to human by sharing 38% amino acid identity and 78% similarity in the ankyrin repeats and SH3 domian and only ASPP family member that identified in Caenorhabditis elegans-lower organism (Bergamaschi et al, 2003). Originally, iASPP was identified as a Rel A/ p65 associated inhibitor (RAI) of 315 amino acids in length (Yang et al, 1999). Subsequent studies demonstrated full length of RAI protein, iASPP containing 828 amino acids in humans and in C. elegans its homologoue is named as Ce-iASPP containing 769 amino acids encoded by ape-1 gene (Bergamaschi et al, 2003;Slee et al, 2004).…”
Section: The Aspp Family Genesmentioning
confidence: 99%
“…[13][14][15] PPP1R13L (protein phosphate 1, regulatory (inhibitory) subunit 13 like, also named RAI or iASPP) encodes an inhibitor of the RelA subunit of NF-κB. 16 It is, therefore, possible that polymorphisms affecting the activity of PPP1R13L could influence the activity of NK-κB.…”
Section: Introductionmentioning
confidence: 99%
“…RAI shares a homologous region with 53BP2, a protein involved in apoptosis regulation. 262 Par-4 (prostate apoptosis response-4) is another recently identified inhibitor of NF-B at the level of IKK and activator of the Fas apoptotic pathway. 263,264 In addition, Par-4 inhibits Bcl-2, a well known anti-apoptotic oncogene.…”
Section: Spotlightmentioning
confidence: 99%